Monitoring Salivary Levels of Interleukin 1 Beta (IL-1β) and Vascular Endothelial Growth Factor (VEGF) for Two Years of Orthodontic Treatment: A Prospective Pilot Study - Hülya Çevik-Aras; Fadimana Isik-Altun; Hatice Kilic-Tok; Julia Naoumova (Mediators of Inflammation)
Background and Objective. Vascular endothelial growth factor (VEGF) and interleukin 1 beta (IL-1β) perform functions in orthodontic tooth movement and can be measured in the saliva. This novel approach is aimed at monitoring continuous changes in IL-1β and VEGF levels in saliva during two years of orthodontic treatment. Material and Methods. Nine healthy females (15-20 years of age) with crowding requiring four premolar extractions and fixed appliances in both jaws were included in this prospective pilot study. A total of 134 stimulated and 134 unstimulated saliva samples were collected during two years of treatment: before tooth extractions (baseline) and then every 6-8 weeks at follow-up appointments. All saliva samples were analysed by the enzyme-linked immunosorbent assay. The mean levels of IL-1β and VEGF were calculated according to the different orthodontic treatment stages: alignment, space closure, and finishing. Repeated analysis of variance (ANOVA) measurements were used to compare the means between different treatment stages. The percentage difference in IL-1β and VEGF between the different treatment stages was analysed by Bland-Altman plots. Results. A gradual increase in IL-1β and VEGF was observed at alignment, reaching significance at space closure (p=0.002 and p=0.025, respectively). At finishing, both IL-1β and VEGF declined, however, without reverting to baseline values (p=0.172 and p=0.207, respectively). Bland-Altman analysis showed the agreement between IL-1β and VEGF in terms of a systematic increase, with a higher percentage difference for VEGF. Conclusions. The salivary levels of both IL-1β and VEGF increased following orthodontic treatment and reached their peaks during the treatment stage of space closure. This novel approach provides a hint on how and when to sample saliva during orthodontic treatment to analyse bone remodelling.